TRANSFER OF LEADERSHIP, MANAGEMENT AND FAMILY RELATIONS BETWEEN GENERATIONS - Atsiilah, Vanindya; Utami, Whidya (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
Family companies are very developed in Indonesia, but not all family companies can survive from generation to generation. In the desire to maintain the company, the first generation must prepare potential successors, to continue the family business so that it continues to grow. Preparing a successor or second generation to replace the position of the first generation is called the succession process. This research aims to determine the succession planning carried out by PT. Mahkota Putri Sejati in leadership transfer, management transfer, and family relationships. This research uses a qualitative approach with a case study method. The type of data used in this research is qualitative data in the form of interviews with informants and observations at the company. There are two sources of data for this research, including primary data in the form of interviews and secondary data in the form of documentation or written data by PT. Mahkota Putri Sejati. The results of this research indicate that the transfer of leadership that has been prepared by the first generation to the next generation of PT. Mahkota Putri Sejati is carried out through learning values ​​and norms which will become the foundation for potential successors. Second, the learning and management transfer process carried out by the first generation to the next generation of PT. Mahkota Putri Sejati is carried out directly involving the company's operational activities. As well as family relationships that were instilled by the first generation in the next generation of PT. Mahkota Putri Sejati by instilling an attitude of mutual respect, respect, and openness to all family members involved.